Ragam Metodologi Memahami Al-Qur'an: Cara Baru Mendekati Ayat Tuhan - Zulkarnaini, Zulkarnaini (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2023)
This article aims to explore various approaches that can be taken in building a paradigm to understand the meaning in the Qur'an. As the guide of mankind, the Qur'an has been uniformly understood throughout its history. The development of the times and the development of science demand new ways of studying the Qur'an, so that reading the Qur'an requires many approaches. Using a qualitative approach, this research uses a literature review. Various references are used related to the theme of the article. The research findings show that there are several methodologies that can be used to build a paradigm basis for understanding the Qur'an. The traditional methodology is the most popular approach because this approach is based on belief. Rational methodology is the basis of the most controversial approach, but very urgent in the development of science. The linguistic methodology becomes an approach that is able to present a very effective explanation of the text of the Qur'an. The hermeneutic methodology, although it is wary of many traditional thinkers, offers a method of understanding the Qur'an contextually.